The Level Of Community Compliance With The Use Of Traffic Signs In Barito Kuala District - Norjannah; Arie Sulistyoko (Interdisciplinary Explorations in Research Journal, 2023)
Abstract This research started from the increasing number of traffic accidents that occurred due to a lack of compliance, understanding and awareness among the public regarding the importance of obeying existing traffic rules and signs, starting from the large number of traffic violations from various ages due to this lack of understanding. The problem that researchers took in this research was regarding "The Level of Community Compliance with the Use of Traffic Signs in Barito Kuala Regency" which was motivated by the increasing number of traffic accidents. The aim of this research is to find out the level of compliance and obstacles of the Barito Kuala community regarding the use of traffic signs. The method used in this research is an empirical legal or sociological method and the type of approach used is a legal sociology approach, namely an approach to studying law in a social context. The results of this research are that the level of community compliance is in categories that fluctuate from data on the number of traffic violations in Barito Kuala Regency in 2021, there were 1,700 cases of violators, while in 2022 there was an increase to 2,787 cases of violations, but in 2023 it decreased to 1,408 cases. violation. Meanwhile, the obstacles faced by the community are lack of knowledge, awareness and understanding of traffic signs, lack of willingness to know traffic signs and never participating in socialization held by the police, especially from traffic police. Keywords: Compliance, Traffic signs, Violations Abstrak Penelitian ini berawal dari semakin meningkatnya angka kecelakaan lalu lintas yang terjadi karena kurangnya kepatuhan, pemahaman dan kesadaran masyarakat akan pentingnya menaati peraturan dan rambu-rambu lalu lintas yang ada, berawal dari banyaknya pelanggaran lalu lintas dari berbagai kalangan usia karena kurangnya pemahaman tersebut. Permasalahan yang peneliti ambil dalam penelitian ini adalah mengenai "Tingkat Kepatuhan Masyarakat Terhadap Penggunaan Rambu Lalu Lintas di Kabupaten Barito Kuala" yang dilatarbelakangi oleh semakin meningkatnya angka kecelakaan lalu lintas. Tujuan dari penelitian ini adalah untuk mengetahui tingkat kepatuhan dan hambatan masyarakat Barito Kuala terhadap penggunaan rambu-rambu lalu lintas. Metode yang digunakan dalam penelitian ini adalah metode hukum empiris atau sosiologis dan jenis pendekatan yang digunakan adalah pendekatan sosiologi hukum, yaitu suatu pendekatan yang mempelajari hukum dalam konteks sosial. Hasil dari penelitian ini adalah tingkat kepatuhan masyarakat berada pada kategori yang berfluktuatif dari data jumlah pelanggaran lalu lintas di Kabupaten Barito Kuala pada tahun 2021 terdapat 1.700 kasus pelanggar, sedangkan pada tahun 2022 mengalami peningkatan menjadi 2.787 kasus pelanggaran, namun pada tahun 2023 mengalami penurunan menjadi 1.408 kasus pelanggaran. Sedangkan kendala yang dihadapi oleh masyarakat adalah kurangnya pengetahuan, kesadaran dan pemahaman tentang rambu-rambu lalu lintas, kurangnya kemauan untuk mengetahui rambu-rambu lalu lintas dan tidak pernah mengikuti sosialisasi yang diadakan oleh pihak kepolisian khususnya dari polisi lalu lintas. Kata kunci: Kepatuhan, Rambu Lalu Lintas, Pelanggaran: Kepatuhan, Rambu Lalu Lintas, Pelanggaran